Neuroimmune Mediators of Pruritus in Hispanic Scalp Psoriatic Itch - Leigh A. Nattkemper; Zoe M. Lipman; Giuseppe Ingrasci; Claudia Maldonado; Juan Carlos Garces; Enrique Loayza; Gil Yosipovitch (Medical Journals Sweden, 2023)
Scalp psoriatic itch is a common, bothersome, yet understudied, condition with numerous associated treatment challenges. The aim of this study was to enhance our understanding of the pathophysiology of scalp psoriatic itch. Immunohistochemical analysis of known neuroimmune mediators of pruritus was conducted using scalp biopsies from 27 Hispanic psoriatic patients. Patients were categorized into mild/moderate or severe itch groups according to their itch intensity rating of scalp itch. Protease activated receptor (PAR2), substance P, transient receptor potential (TRP)V3, TRPM8 and interleukin-23 expression all correlated  significantly with itch intensity. The pathophysiology of scalp psoriasis is largely non-histaminergic, mediated by PAR2, interleukin-23, transient receptor potential channels, and substance P.